Cultural adaptation, content validity and inter-rater reliability of the "STAR Skin Tear Classification System" - Kelly Cristina Strazzieri-Pulido; Vera Lúcia Conceição de Gouveia Santos; Keryln Carville (Universidade de São Paulo, 2015)
AIMS: to perform the cultural adaptation of the STAR Skin Tear Classification System into the Portuguese language and to test the content validity and inter-rater reliability of the adapted version.METHODS: methodological study with a quantitative approach. The cultural adaptation was developed in three phases: translation, evaluation by a committee of judges and back-translation. The instrument was tested regarding content validity and inter-rater reliability.RESULTS: the adapted version obtained a regular level of concordance when it was applied by nurses using photographs of friction injuries. Regarding its application in clinical practice, the adapted version obtained a moderate and statistically significant level of concordance.CONCLUSION: the study tested the content validity and inter-rater reliability of the version adapted into the Portuguese language. Its inclusion in clinical practice will enable the correct identification of this type of injury, as well as the implementation of protocols for the prevention and treatment of friction injuries.